Public Complaint Services: How Designing Integrated Services for Websites, Email and Social Media Can Increase Public Trust - Yono Maulana; Ratih Hurriyati; Firman Hidayat (Ridwan Institute, 2023)
Analyzing and identifying potential improvements in public complaint services in Indonesia through designing and integrating integrated Dumas Presisi services involving websites, email and social media. This research uses a quantitative and qualitative approach with case studies as the main method. Data was collected through online surveys, interviews via electronic messaging and documentation analysis used to support this research. The results of the research can be concluded that 42.30% of the public consider Dumas Presisi to be quite fast in responding to complaints with good follow-up quality, with the ease of use of the Dumas Presisi application being quite good, able to give confidence to the public that their reports will be followed up, speed, easy data transactions and the security provided makes people feel comfortable when using the Dumas Presisi application.